Influence of TNF-alpha blockers on the oral prevalence of opportunistic microorganisms in ankylosing spondylitis patients - Pereira, D. F. A. [UNESP]; Pinheiro, M. M.; Silva, P. N. F.; Teodoro, G. R.; Brighenti, Fernanda Lourenção [UNESP]; Koga-Ito, C. Y. (Clinical & Exper Rheumatology, 2012)
ObjectivesTo compare the oral prevalence and antimicrobial susceptibility of candida spp. staphylococci, enterobacteriaceae, and pseudomonas spp. from ankylosing spondylitis (AS) patients receiving conventional and anti-TNF-alpha therapy.MethodsThe study included 70 AS patients, diagnosed according to the modified New York criteria (1984). The volunteers were divided into 2 groups: a biological group (AS BioG) (n=35) (on anti-TNF-a therapy) and a conventional group (AS ConvG) (n=35). The control group (ContG) (n=70) was made up of healthy individuals matched for age, gender, and oral conditions. After clinical examination, oral rinse samples were collected and plated in specific culture media. The number of colony-forming units per milliliter (cfu/ml) was obtained, and isolates were identified using the API system. Antimicrobial susceptibility tests were performed according to the NCCLS guidelines. Prevalence and counts of microorganisms were statistically compared between the 3 groups, using the Mann-Whitney and Chi-square tests. Significance level was set at 5%.ResultsIn both the AS BioG and the AS ConvG, staphylococci counts were higher than that in the ContG (p<0.0001).Candida albicans and staphylococcus epidermidis were the most commonly found species in all the groups. Serratia marcescens and klebsiella oxytoca were more prevalent in the AS BioG and the AS ConvG, respectively. Two candida isolates (2.8%) from the AS BioG and 5 (10.8%) from the AS ConvG were resistant to amphotericin B and 5-fluorocytosine. A low percentage of staphylococci isolates was resistant to amoxicillin, ciprofloxacin, and doxycycline.ConclusionHigher counts of staphylococci were observed in both AS groups, regardless of the current therapy, age, sex, and oral conditions. Anti-TNF-alpha therapy could not be correlated with increased counts of microorganisms.
Keywords: ankylosing spondylitis; infection; super-infection; oral microbiology; TNF-alpha blockers; candida; staphylococcus